Factors affecting profitability of life insurance companies - Suraj Khatiwada (Journal of Corporate Finance Management and Banking System, 2026)
The study involves the evaluation and analysis of the effects of independent variables on the profitability of life insurance companies in Nepal. The descriptive research design has been adopted. In this study, descriptive statistics, bivariate correlation and linear multiple regression mode are selected to measure the effects of explanatory variables on the dependent variable. The data are taken from annual reports of selected life insurance companies and other websites. This study is based on the four life insurance companies for the period of FY 2069/70 to 2078/79. In this study, the convenience sampling technique is used. The correlation and multiple regression analysis are used to examine the relationship between independent and dependent variable. In this study, ROA is taken as the dependent variable and ROCE, LR, SIZE, FL and ER are taken as the independent variable. This paper investigates the impact of ROCE, LR, SIZE, FL and ER on profitability of selected life insurance companies. The study reveals that, FL and ROCE have significant positive relation and meanwhile ER has significant negative relation with ROA of life insurance companies.